Basic properties of low thermal expansion coefficient (Y0.5Ca0.5)1−xInxBaCo3ZnO7+δ (x=0, 0.1, 0.2, 0.3) solid solutions for solid oxide fuel cell cathode materials. (December 2022) - Zhou, Qingjun; Wang, Yajie; Yang, Xin; Bu, Fanxing; Yang, Feiran; Wang, Mingchao; li, Yan
Highlights: A series of YCIx BCZ cathodes have been studied systematically. Thermal expansion coefficients of YCIx BCZ are lower than some cobalt-containing cathodes. The YCIx BCZ cathodes show active catalysis on oxygen reduction reaction. The YCI0.2 BCZ cathode displays excellent phase stability and CO2  tolerance. Abstract: In this investigation, In-doped (Y0.5 Ca0.5 )1−x Inx BaCo3 ZnO7+δ ( x  = 0, 0.1, 0.2, and 0.3, abbreviated as YCIx BCZ) swedenborgite oxides are successfully prepared, and the effects of In-doping on phase structure, electrical conductivity, TEC, thermal stability and electrochemical properties are investigated thoroughly. The partial substitution of In for Y and Ca has a slight effect on the phase structure, electrical conductivity, TEC and area-specific resistance (ASR) of YCIx BCZ. All the YCIx BCZ samples investigated show an excellent tolerance to CO2 at 800 °C. Additionally, the YCI0.2 BCZ phase are stable after 72 h exposure to air at 600, 700, and 800 °C, separately, while YCIx BCZ ( x  = 0, 0.1 and 0.3) show instability at 700 °C in air. The optimal composition, YCI0.2 BCZ, exhibits a relatively low ASR value (0.048 Ω cm 2  at 800 °C) and a high power density (345 mW cm −2  at 800 °C). The current results demonstrate that YCI0.2 BCZ is promising cathode material for IT-SOFCs. Graphical abstract: Image, graphical abstract